Psychological Trauma of Alice Hart as the Main Character in Glendyn Ivin’s The Lost Flowers of Alice Hart (2023) - Oktafiani, Lutfiah Tri; Ariyani, Latifah Dwi (Metaphor, 2025)
This research aims to analyze: 1) the traumatic experiences affect Alice Hart’s psychological condition in the film The Lost Flowers of Alice Hart (2023), and 2) the psychological reconciliation the character of Alice Hart in the film The Lost Flowers of Alice Hart (2023). This research uses a descriptive qualitative method to analyze the film of The Lost Flowers of Alice Hart (2023) directed by Glendyn Ivin as the objective research. The data collection methods include watching, reading, identifying, classifying, and selecting. The researcher utilized Sigmund Freud’s psychoanalysis to analyze the data through steps of displaying, explaining, and interpreting. The result of this research shows that: 1) the traumatic experiences affect Alice Hart’s psychological condition are traumatic memory, traumatic reaction of grief, panic attack as a reaction to Alice’s trauma, Alice’s anger, and Alice’s emotional reaction, 2) the psychological reconciliation the character of Alice Hart in film The Lost Flowers of Alice Hart (2023) are group support, art therapy, nature therapy.